"Abracadabra!" the magic of poetic healing. Issue 4 (2nd October 2017) - Reiter, Sherry
ABSTRACT: The author explores the connection between magic and poetry therapy, examining the two key principles of magic, the isoprinciple, and the principle of opposites. Other components include imagery, condensation, and displacement. Examples are given to demonstrate the magic of metaphor. "Abracadabra" is an age-old incantation, the roots of which may hold significance for magicians as well as poetry therapists.